Estrutura espacial da assembleia de cupins (Isoptera) em uma área de cerrado sensu stricto do Parque Estadual da Serra de Caldas Novas, Goiás - OLIVEIRA, Danilo Elias de (2009)
One of the major community ecology's objectives is to understand the factors that determine the spatial distribution of populations of different species belonging to an assembly. Works that investigate these causal factors on the termite fauna are rare, and to the Cerrado region, non-existent. This work aims to 1) describe the spatial structure of the termite assembly in a cerrado sensu stricto area, 2) verify whether there is spatial autocorrelation in the composition of termites and 3) whether the species are distributed on a checkerboard, and if so, what cause this distribution. On the plateau of Parque Estadual da Serra de Caldas Novas (PESCAN), I sampled the termites on 123 10m2 plots with distances to each other varying from 5 m to 3.5 km. This plots were divided into two sets, One of those arranged into 3 transects of 28 plots each and the other arranged into 13 triads distant 1 km to the next. I Identified the species and grouped them into food guilds. I made a Mantel s autocorrelogram with 10 distance classes to assess the changes in the similarity of the composition in function of space. I compared the C-score index, using the entire assembly and each guild alone, with a null distribution (with 5000 randomizations) to check whether there is a checkerboard distribution in the assembly and what its cause. I found 579 colonies of 57 species of termites, most of which was humivorous. There was no significant spatial autocorrelation in any distance class concerning the species composition because the values of r of Mantel for all distance classes were close to zero and not significant. The C-score was significant for the assembly as a whole (C-score = 52.01, p = 0.006), but was not significant for any of the guilds. The cerrado of PESCAN is one of the areas with the highest species diversity already registered for the Cerrado biome and possibly this is because of the well preserved condition of the park and the sampling effort employed. The absence of spatial autocorrelation indicates that the species of termites are distributed in space regardless of the distribution of others. This is the first study that shows that the assembly of termites is distributed on a checkerboard and that this is due to historical events of dispersal and colonization. In the area I studied, probably the dispersion of the allates during flight events makes the establishment of future colonies in a field forming a "scrambled" and not superimposed distribution known as checkerboard distribution. These results contradict the recurrent idea that intra and interspecific competition is the causal factor of the colonies spatial distribution of termites.